Transplantation of Marginal Organs: Immunological Aspects and Therapeutic Perspectives in Kidney Transplantation - Noble, Johan; Jouve, Thomas; Malvezzi, Paolo; Süsal, Caner; Rostaing, Lionel (Frontiers in Immunology, 2020)
Recent data from the World Population Prospects projects that by 2050, nearly all regions in the world will have a quarter or more of the population aged 60 and above. Chronic kidney disease (CKD) has a high global prevalence (around 13%) worldwide and the prevalence of CKD and end-stage kidney disease (ESKD) increase with age. Kidney transplantation remains the best therapeutic option for ESKD, offering a survival benefit in comparison with dialysis maintenance for most patients. This review focuses on immunological aspects of kidney transplantation in older patients and marginal donors i.e. 60 years or older deceased kidney donors or 50 to 59 years old deceased kidney donors with comorbidities. Clinical outcomes of kidney recipients in term of renal and patient survival are more than acceptable even for patients over 70. In this population, the first cause of graft loss is death with a functional graft. However, the inherent issues of these transplantations are the acceptance or refusal of frail kidney from old donor, the increased immunogenicity of these organs in balance with potential frail and immunosenescent recipients. Finally, the immunosuppressive regimen itself is a challenge for the future of the transplant, in order to prevent adverse effects such as nephrotoxicity, higher risk of infections or cancer in a population already at risk. Belatacept may have a good place in the immunosuppressive strategy to improve efficacy and the safety post-transplantation.